The many “costs” of transportation: Examining what cancer caregivers experience as transportation obstacles - Thomson, Maria D.; Van Houtven, Courtney Harold; Xu, Rebecca; Siminoff, Laura A. (Cancer medicine (Malden, MA), 2023)
Background Transportation has been identified as a specific source of burden for cancer caregivers. This study examined cancer caregivers' subjective experiences and objectives costs associated with transportation over a 6‐month period of providing end‐of‐life care to a family member or friend. Methods This was a multi‐site longitudinal, prospective cohort study that followed 223 caregiver–patient dyads. Data were collected using biweekly, semi‐structured interviews for up to 6 months and collection of all caregiving related receipts. Interviews were coded and analyzed using a comparative, iterative analysis and actual out of pockets costs were described using descriptive statistics. Results Over the 6‐month study period most caregivers (n = 143; 74%) discussed transportation at one or more timepoints. Average biweekly transportations costs to caregivers were $43.6. Caregivers described (n = 56; 39%) multiple direct and indirect costs of transportation, and 58% (n = 84) discussed the need for transportations services or assistance at the institutional level. Conclusions Caregivers described the multifaceted costs of transportation they experienced which are in line with previous work. Alongside descriptions of direct costs, caregivers described key opportunity costs, such as personal and work time forgone to transporting patients. Caregivers also made suggestions for institutional and/or civic based solutions to facilitate reliable modes of transportation, rather than individual‐level intervention.